Mouse Model of Chromosome Mosaicism Reveals Lineage-Specific Depletion of Aneuploid Cells and Normal Developmental Potential. Issue 11 (November 2016) - Bolton, Helen; Graham, Sarah J. L.; van der Aa, Niels; Kumar, Parveen; Theunis, Koen; Gallardo, Elia Fernandez; Voet, Thierry; Zernicka-Goetz, Magdalena
Abstract : (Abstracted from Nat Commun 2016;7:11165) Most human preimplantation embryos display chromosome mosaicism. In the most common pattern of mosaicism, the embryo is chimeric (containing both euploid and aneuploid cells).